Little strokes fell big oaks: The use of weak magnetic fields and reactive oxygen species to fight cancer - Margit Egg; Thomas Kietzmann (Redox Biology)
The increase in early-stage cancers, particularly gastrointestinal, breast and kidney cancers, has been linked to lifestyle changes such as consumption of processed foods and physical inactivity, which contribute to obesity and diabetes - major cancer risk factors. Conventional treatments such as chemotherapy and radiation often lead to severe long-term side effects, including secondary cancers and tissue damage, highlighting the need for new, safer and more effective therapies, especially for young patients.Weak electromagnetic fields (WEMF) offer a promising non-invasive approach to cancer treatment. While WEMF have been used therapeutically for musculoskeletal disorders for decades, their role in oncology is still emerging. WEMFs affect multiple cellular processes through mechanisms such as the radical pair mechanism (RPM), which alters reactive oxygen species (ROS) levels, mitochondrial function, and glycolysis, among others.This review explores the potential of WEMF in conjunction with reactive oxygen species as a cancer therapy, highlighting WEMFs selective targeting of cancer cells and its non-ionizing nature, which could reduce collateral damage compared to conventional treatments. In addition, synchronization of WEMF with circadian rhythms may further enhance its therapeutic efficacy, as has been demonstrated in other cancer therapies.